Pemberdayaan Masyarakat melalui Instalasi dan Edukasi Pemeliharaan Penerangan Jalan Umum Tenaga Surya (PJUTS) di Desa Tepansari sebagai Upaya Mewujudkan Kemandirian Infrastruktur - Danang Isworo Wijayanto; Mufthi Amartia Arbi; Vionny Vionny; Mizana Amaliya; Safitri Wanci Ratri; Annisa Kamila Zahro; Muhammad Wawan Fuadul A; Muhammad Zainul F; Nurul Fajriyah; Rizal Luthfi M; Atik Atina R; Adi Prasetyo; Dwi Cahyo S; Muhammad Subagio; Asri Septi Mutiani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The lack of street lighting infrastructure on the connecting roads between hamlets in Tepansari Village hinders community mobility and increases security risks at night. This community service program aims to implement Solar Power Street Lighting (PJUTS) technology as a renewable energy solution while building infrastructure independence through community empowerment. The implementation method uses the Asset-Based Community Development (ABCD) approach which includes five stages: discovery, design, define, delivery, and destiny. The program involved a collaboration between 7 KPM students, 2 village officials, and 10 local residents. The results of the service show that two PJUTS units have been successfully installed at strategic points and are functioning optimally independently without the burden of village electricity costs. In addition to physical outputs, this activity succeeded in increasing the technical capacity of residents in preventive maintenance of solar panel and battery components through a learning-by-doing process. The immediate impact felt by the community is an increased sense of security and mobility comfort, which supports social-religious and economic activities at night. This program proves that the integration of appropriate technology and participatory empowerment is an effective strategy in realizing sustainable rural infrastructure independence in accordance with SDGs point 7 targets.